The role of social capital in COVID-19 deaths - Janaki Imbulana Arachchi; Shunsuke Managi (BMC, 2021)
Abstract Background The COVID-19 pandemic has shown a continuously increasing trend with a large variation in the number of COVID-19 deaths across countries. In response, many countries have implemented non pharmaceutical methods of intervention, such as social distancing and lockdowns. This study aims to investigate the relationship of four dimensions of social capital (community attachment, social trust, family bond, and security) and several control variables with COVID-19 deaths. Methods We retrieved data from open access databases and a survey. COVID-19 death-related data were collected from the website "Centre for Systems Science and Engineering (CSSE) at Johns Hopkins University". Social capital-related data were collected from a large-scale survey that included web-based and face-to-face surveys covering 100,956 respondents across all regions/provinces/states of 37 countries in 2017. Data regarding population density, number of hospital beds, and population aged 65 or older were retrieved from the World Development Indicators (WDIs). Data on country lockdowns were obtained from the website "National responses to the 2019-20 coronavirus pandemic". Linear regressions were applied to identify the relationship between social capital and COVID-19 deaths. Results We found that COVID-19 deaths were associated with social capital both positively and negatively. Community attachment and social trust were associated with more COVID-19 deaths, and family bond and security were associated with fewer deaths. COVID-19 deaths were positively associated with population density, ageing population, and interactions between four dimensions of social capital-related factors and the ageing population. Furthermore, the number of hospital beds and early lockdown policy were negatively associated with COVID-19 deaths. Conclusions The results indicate that the role of social capital in dynamically evolving threats, such as the current COVID-19 pandemic, is not always negative or positive. Therefore, people's behaviour should be changed to support countries' response to the COVID-19 threat.